Bacterial diversity amplifies nutrient‐based plant–soil feedbacks. (20th April 2015) - Weidner, Simone; Koller, Robert; Latz, Ellen; Kowalchuk, George; Bonkowski, Michael; Scheu, Stefan; Jousset, Alexandre
Summary: Plants foster diverse assemblages of bacteria in the rhizosphere serving important functions which may result in enhanced plant growth. Microbial diversity is increasingly recognized to shape the functionality of microbial communities. This leads to the assumption that there is a positive relationship between rhizosphere diversity and plant growth. Here we investigate how bacterial diversity affects the mineralization of organic matter and plant nutrient acquisition. We hypothesized that altered bacterial diversity will affect nitrogen mineralization, uptake by plants and ultimately plant growth. We set up a controlled model system with Arabidopsis thaliana colonized by defined assemblages of fluorescent pseudomonads, a well‐characterized plant‐beneficial rhizosphere taxon. The growth substrate contained casein as sole nitrogen source, making the plant nitrogen uptake dependant on breakdown by bacterial enzymes. Bacterial diversity was associated with a higher enzyme activity which increased nitrogen mineralization and enhanced plant growth. The effect of bacterial diversity on plant growth increased with time, pointing to a positive feedback between bacteria and plants: bigger plants associated with species‐rich bacterial communities supported more bacterial growth, which further enhanced the impact of bacteria on plant growth. We demonstrate that plant–soil feedbacks establish rapidly during one single growth season and that bacterial diversity modulates this interaction. Preserving soil microbial diversity therefore may improve positive plant–soil feedbacks and thereby plant growth. Abstract : Lay Summary